Casualisation of Work and Employees’ Satisfaction in the BUA Group of Companies, Lagos, Nigeria - Fasanmi, Olumuyiwa Oladapo; Sodeinde, Gbemi Moses Sodeinde; Babatunde, Bayode Olusanya Babatunde; Alabi, Williams Omodara Alabi; Alabi, Bolatito Boladale Alabi (African Journal of Stability and Development (AJSD), 2024)
Casualisation of work in the globe and certainly in Nigeria is in contrast to the labours’ tenets as this has most often resulted in conflict between employees, their unions, and employers across different workplaces in Nigeria and the world at large. The study investigated the impact of casualisation of work on employees’ job satisfaction in the BUA Group of Companies, Lagos, Nigeria. This was done with a population of 864 and sample size of 273. The hypotheses of the study were tested with the use of Pearson Correlation statistical tool. Findings of the study exhibited a positive significant impact of: temporary employment on staff’s personal growth; and non-standard employment on workers’ job competency in BUA Group of Companies, Lagos. It was concluded that casual workers in the organisation used to enjoy some measures of cares that are given to their permanent counterparts. The study, then recommended stern measures by the Nigerian Government at all levels to make sure that workplaces in the country comply with the provisions of the 2010 Casualisation Prohibition Bill which is capable of guaranteeing equal rights to all workers.